A novel method for determination of the 15N isotopic composition of Rubisco in wheat plants exposed to elevated atmospheric carbon dioxide. Issue 2 (5th November 2014) - Aranjuelo, Iker; Molero, Gemma; Avice, Jean Christophe; Bourguignon, Jacques
<x xml:space="preserve">Abstract</x> Although ribulose‐1, 5‐bisphosphate carboxylase/oxygenase (Rubisco) is mostly known as a key enzyme involved in CO2 assimilation during the Calvin cycle, comparatively little is known about its role as a pool of nitrogen storage in leaves. For this purpose, we developed a protocol to purify Rubisco that enables later analysis of its 15N isotope composition (δ15N) at the natural abundance and 15N‐labeled plants. In order to test the utility of this protocol, durum wheat (Triticum durum var. Sula) exposed to an elevated CO2 concentration (700 vs 400 µmol mol−1) was labeled with K15NO3 (enriched at 2 atom %) during the ear development period. The developed protocol proves to be selective, simple, cost effective and reproducible. The study reveals that 15N labeling was different in total organic matter, total soluble protein and the Rubisco fraction. The obtained data suggest that photosynthetic acclimation in wheat is caused by Rubisco depletion. This depletion may be linked to preferential nitrogen remobilization from Rubisco toward grain filling.